The fractal organization of ultradian rhythms in avian behavior - Guzmán, Diego Alberto (2017)
Fil: Guzmán, Diego Alberto. Universidad Nacional de Córdoba. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.